In Silico Analysis of Green Tea Polyphenols as Inhibitors of AChE and BChE Enzymes in Alzheimer’s Disease Treatment - Ali, Babar; M.S. Jamal, Qazi; Shams, Saiba; A. Al-Wabel, Naser; U. Siddiqui, Mughees; A. Alzohairy, Mohammad; A. Al Karaawi, Mohammed; Kumar Kesari, Kavindra; Mushtaq, Gohar; A. Kamal, Mohammad (CNS & Neurological Disorders - Drug Targets, 2016)
Alzheimer’s disease (AD) is the most frequent cause of dementia, especially in the elderly. AD is the most common progressive neurodegenerative disorder, which involves the loss of structure and function of cholinergic neurons. Moreover, if these neuronal changes cannot be compensated, this may ultimately lead to neurodegenerative processes. Therefore, most of the drug therapies are based on the cholinergic hypothesis, which suggests that AD begins as a deficiency in the production of the neurotransmitter acetylcholine. In this context, many inhibitors play an important role in AD treatment among which acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) have more potential in the treatment process of AD. In this study, we selected tea polyphenols of green tea which are reported as AChE and BChE inhibitors used in the treatment of AD. The molecular docking results revealed that polyphenols exhibit interactions and inhibit by binding with AChE and BChE. The amount of energy to bind with AChE and BChE needed by Epigallocatechin-3-gallate was lowest at about -14.45 and -13.30 kcal/mol, respectively. All compounds showed binding energy values ranging between -14.45 to -9.75 kcal/mol for both types of enzymes. The present docking study suggests that tea polyphenols inhibit AChE as well as BChE and enhance the cholinergic neurotransmission by prolonging the time. However, AChE molecules remain in the synaptic cleft. In consideration to these findings, cholinesterase inhibitors are suggested as the standard drugs for the treatment of AD.
Keywords: butyrylcholinesterase